Caracterización cromohipológica y morfométrica de los caballos criollos en el cantón El Carmen de la provincia de Manabí - Barreto Zambrano, Edwin Alexander (2021)
The present work was carried out in Wilfrido Loor Moreira parish (Maicito) belonging to El Carmen canton, and consisted of the chromohypological and morphometric characterization of a sample of 140 Creole horses between mares and horses older than 3 years. They were measured with tape and zoometric rods of different sizes. By means of descriptive statistics, the following averages were determined in zoometric variables: height at the withers 134.03cm (± 5.71), height at the croup 134.80cm (± 5.85), length of the head 54.22cm (± 2.72), head width 19.97cm (± 0.81), longitudinal diameter 136.76cm (± 7.06), dorso-sternal diameter 61.55cm (± 3.06), bicostal diameter 34,26cm (± 3.30), croup length 41.54cm (± 3.77), croup width 44.55cm (± 3.06), chest circumference 153.91cm (± 8.11), perimeter of the cane 18.95cm (± 1.23). Zoometric indices were calculated and by frequencies these specimens were classified as: mesocephalic, longilinear, dolichothoracic, dolichopelvic, dolichomorphic relative depth, high metacarpal correlation, and long proportionality with mean sacrum hip angle and proximal weight 294.05kg (± 45.77). In the external variables the rectilinear head profile (87.14%), pyramidal cervical profile (90.71%), normal dorso-lumbar profile (100%) and normal ventral profile (95.00%) prevailed. Chromohypologically the chestnut coat predominated (43.57%), with respect to the coloration of the hooves, 67.14% of the animals wore black hooves on all four limbs. The results found correspond to the chromohypological and morphometric characteristics of the Ecuadorian Creole horse.